MAIN TASKS PROJECT MANAGEMENT MODERNIZATION IN THE AVIATION TECHNOLOGY PARK - Самков, О. В.; Качур, С. Ю.; Височанський, А. С.; Корнієнко, О. В (Science-based technologies, 2009)
Possibility of application of the applied package of Microsoft Project is examined for the decision of tasks of projects management during modernization of park of aerotechics. The method of redistribution of resources of project is offered with the purpose of cutback of spending time on his leadthrough.